2022
DOI: 10.1002/adfm.202203022
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Horizontal Dipole Orientation Induction for Highly Efficient and Spectral Stable Thermally Activated Delayed Fluorescence White Organic Light‐Emitting Diodes

Abstract: Radiative exciton generation and light out-coupling are two crucial factors for highly efficient organic light-emitting diodes (OLEDs). Herein, a thermally activated delayed fluorescence (TADF) material DspiroS-TRZ with high horizontal dipole ratio (HDR, Θ // = 82%) is utilized as the blue emitter as well as the host for an orange-red TADF emitter TPA-AQ to fabricate white OLEDs. A synergetic horizontal dipole orientation induction on the transition dipole moment of TPA-AQ is achieved by the highly orientated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Solution-processable organic light-emitting diodes exhibit a maximum external quantum efficiency of 24.74%. This study provides a universal strategy for designing highperformance TADF emitters through molecular packing and excited state regulation.With a theoretical internal quantum efficiency (IQE) of 100%, thermally activated delayed fluorescence (TADF) materials without noble heavy metals are considered the next-generation emitting materials for organic light-emitting diodes (OLEDs) [1][2][3][4][5][6] . Characterized by the reverse intersystem crossing (RISC) process from triplet state (T 1 ) to singlet state (S 1 ), TADF emitters can thus achieve high-performance OLEDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Solution-processable organic light-emitting diodes exhibit a maximum external quantum efficiency of 24.74%. This study provides a universal strategy for designing highperformance TADF emitters through molecular packing and excited state regulation.With a theoretical internal quantum efficiency (IQE) of 100%, thermally activated delayed fluorescence (TADF) materials without noble heavy metals are considered the next-generation emitting materials for organic light-emitting diodes (OLEDs) [1][2][3][4][5][6] . Characterized by the reverse intersystem crossing (RISC) process from triplet state (T 1 ) to singlet state (S 1 ), TADF emitters can thus achieve high-performance OLEDs.…”
mentioning
confidence: 99%
“…With a theoretical internal quantum efficiency (IQE) of 100%, thermally activated delayed fluorescence (TADF) materials without noble heavy metals are considered the next-generation emitting materials for organic light-emitting diodes (OLEDs) [1][2][3][4][5][6] . Characterized by the reverse intersystem crossing (RISC) process from triplet state (T 1 ) to singlet state (S 1 ), TADF emitters can thus achieve high-performance OLEDs.…”
mentioning
confidence: 99%
“…Since the EQE max datum of an OLED correlates not only with the PLQY of the emitting layer and the electron-hole balance ratio (γ e-h ), but also with the EUE and the light out-coupling efficiency (η out ) (EQE = γ e-h × φ PL × EUE × η out ) 14 , to gain insight into the reasons for the lower EQE max of Device A than Device B, firstly, horizontal dipole measurements together with optical simulation were carried on CzNI and TPANI [34][35][36] . The results indicated that the neat film samples of CzNI and TPANI showed nearly identical horizontal dipole ratios (Θ // , 86% vs. 85%, vide Fig.…”
Section: Photophysical and Electroluminescent Propertiesmentioning
confidence: 99%
“…Research on the development of white organic light-emitting diodes (WOLEDs) is flourishing owing to their great potential in environmentally friendly and energy-saving solid-state lighting technology. [1][2][3][4][5][6][7][8] WOLEDs constructed using complementary colors can obtain stable electroluminescence (EL) spectra along with a relatively simple device configuration and fabrication process. For the realization of high-performance WOLEDs, efficient orange-red emission is an essential component, [9][10][11] however, the exploration of such materials is particularly imperative and remains challenging due to the intrinsic poor emission caused by the energy gap law and the concentration quenching effect in the solid-state.…”
Section: Introductionmentioning
confidence: 99%